Further Contribution to the Monotypic Genera of Angiosperms in Indian Flora - Khanna, K. K.; Kumar, Anand (Indian Forester, 2016)
The paper deals with enumeration of 39 monotypic genera of angiosperms occurring in India. The present list is an addition to 189 monotypic genera earlier reported from Indian flora thus totalling the list to 228.